Responsabilidade tributária de grupos econômicos - Stamm, Bruno Barbosa (2022)
The objective of this study is to analyze whether there is legal foundation in imputing tax liability to legal entities which are constituted within a common economic group. Firstly, some general tax liability analysis is conducted, emphasizing its constitutional limitations imposed on the appointment of the taxable person. Subsequently, each provision contained within the Brazilian Tax Code (CTN) is analyzed, which are commonly invoked in the attempt of generating liability for other legal entities constituent of an economic group, intending to identify their application hypotheses. After that, the concept of an economic group is established in the light of its applicability in Tax Law, being a group of legal people that conserve their asset autonomy aiming the achievement of a common objective, through a single direction and submission to a unique corporate policy. Having set the concept, its compatibility is verified according to the rules present in the Brazilian Tax Code and it is explored whether article 50 of the Civil Code is applicable in Tax Law. Finally, the jurisprudence of the Superior Court of Justice is analyzed, by comparing the Court's current understanding of the theme with the premises and conclusions established throughout the present study. At last, it is concluded that it is possible to apply article 50 of the Civil Code, according to the authorization of article 149, VII, of the Brazilian Tax Code, regarding tax assessment, actually expanding the hypotheses for defense of liable companies